Rancangan Kapal Penyeberangan Optimal pada Lintasan Kasipute - Pising - Andi Dirga Noegraha (Celebes Engineering Journal, 2019)
The aim of this research is to obtain the optimal dimension of ferry vessels on the Kasipute-Pising crossing. This research is quantitative using a research design based on work procedures from quantification to measure research variables through the selection and design of data structures. By identifying problems and mismatches of ships operating with the main purpose of crossing transportation, and determining objective functions of optimization. Then determine the aspects of ship design that are adjusted to the characteristics of crossing vessels based on the conditions of request, oceanography and infrastructure. The optimal dimension of the crossing vessel for the Kasipute - Tanjung Pising crossing path has been obtained with dimensions of Length Overall 45.11 m, Breadth 11.9 m, Height of ship 2.7 m, Draft 1.78 m, speed 13 knots, tonnage 451 GT, passenger 450 people, 15 units of R-4 vehicles. The direction of optimization of the ship's design is more emphasized on increasing the speed and effectiveness of the passenger load capacity and mare space of R-4.